2015
DOI: 10.3109/10428194.2015.1071488
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring for either oral or intravenous busulfan when combined with pre- and post-transplantation cyclophosphamide

Abstract: Busulfan (Bu)/cyclophosphamide (Cy) is a standard conditioning platform for allogeneic transplantation. We developed a strategy separating the Cy into two pre/post-transplantation doses (PTCy), providing myeloablative conditioning and single-agent graft-versus-host disease (GVHD) prophylaxis. We investigated the impact of Bu route on treatment-related toxicity for 131 consecutive adult patients. Busulfan was administered in four daily divided doses either orally (n = 72) or intravenously (n = 59) with pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…As noted in FAQ3, whether patients in this study received BU TDM is unknown, but a survey of centers done shortly after the study suggested 50% to 60% of the centers who reported to CIBMTR used BU TDM [48]. This analysis contrasts with results that have not noted any increased risk in relapse rates when comparing similar regimens that differed only by the route of BU administration [67][68][69][70]. The effect of the administration route on SOS has also not been consistent: some reports found a significantly higher rate of SOS after oral BU when compared with after i.v.…”
Section: Faq4: Is Oral or Intravenous Bu Preferred? IV Bu Tends To mentioning
confidence: 75%
See 1 more Smart Citation
“…As noted in FAQ3, whether patients in this study received BU TDM is unknown, but a survey of centers done shortly after the study suggested 50% to 60% of the centers who reported to CIBMTR used BU TDM [48]. This analysis contrasts with results that have not noted any increased risk in relapse rates when comparing similar regimens that differed only by the route of BU administration [67][68][69][70]. The effect of the administration route on SOS has also not been consistent: some reports found a significantly higher rate of SOS after oral BU when compared with after i.v.…”
Section: Faq4: Is Oral or Intravenous Bu Preferred? IV Bu Tends To mentioning
confidence: 75%
“…The effects of oral versus i.v. BU on efficacy, toxicity, and pharmacokinetics on the outcomes of allogeneic HCT have been analyzed retrospectively [48,53,[63][64][65][66][67][68]. These studies are often confounded by heterogeneous patient populations, the use of BU TDM for only 1 of the administration routes, differences in the other conditioning regimen components, and BU exposure data not being available.…”
Section: Faq4: Is Oral or Intravenous Bu Preferred? IV Bu Tends To mentioning
confidence: 99%
“…The conditioning used prior to HSCT, mainly Bu‐based conditioning, is one of the most common causes of these toxicities and several strategies have been introduced to improve clinical outcome. Several serious complications, such as elevated liver enzymes, SOS, hemorrhagic cystitis, interstitial pneumonia, and mucositis have been correlated to high‐dose Bu …”
Section: Discussionmentioning
confidence: 99%
“…Several serious complications, such as elevated liver enzymes, SOS, hemorrhagic cystitis, interstitial pneumonia, and mucositis have been correlated to high-dose Bu. 1,2,18,28,29 In our center, we have developed several strategies over more than 20 years to reduce the incidence of the serious adverse effects, mainly SOS, improving both the clinical outcome and the patients' quality of life. Among patients receiving conventional Bu-based myeloablative conditioning prior to HSCT, the incidence of SOS decreased dramatically during 1995-2015.…”
Section: Discussionmentioning
confidence: 99%
“…2 Supratherapeutic concentrations lead to lethal toxicity, including pulmonary toxicity, 3 hepatic veno-occlusive disease, 4,5 and seizures, 6 while subtherapeutic concentrations lead to graft rejection and disease relapse. 7 Therapeutic drug monitoring (TDM) can reduce the incidence of seizures. 6 In addition to the narrow therapeutic index, specific busulfan exposures have been associated with important clinical outcomes in HCT patients.…”
mentioning
confidence: 99%